MENINGKATKAN PEMAHAMAN DAMPAK TINDAKAN BULLYING DI LINGKUNGAN SEKOLAH SMP TAMAN SISWA BATU - Puspita Pebri Setiani; Ali Badar; Tirza Priscilla Alfianto; Uyunul Akbar Ramadani (JPM PAMBUDI, 2023)
Bullying has always been a hot topic of conversation. Bullying is an action taken by a person to hurt, mentally drop another person by committing violence so that the victim receives all forms of treatment from the bully (Yonita & Karneli, 2019). The impact of bullying is very large, the victim can become depressed and traumatized so that in the future the victim will close himself off from outside influences and feel devastated and eventually commit suicide. The Minister of Education and Culture (Mendikbud) Nadiem Makarim explained the results of the character survey that had been conducted. The survey involved 260 thousand schools in Indonesia at the elementary/madrasah to high school/vocational school levels. There were 6.5 million students and 3.1 million teachers involved in the survey. From the survey, there was 24.4 percent of the potential for bullying in schools. In an effort to serve to increase understanding of the impact of bullying at Taman Siswa Batu Middle School, the method used was a socialization which was held on Tuesday 14 February 2023. So the results of the socialization increased the understanding of students and teachers at Taman Siswa Middle School, Batu City about the effects of bullying.